Biosynthesis of silver nanoparticles by Pseudomonas spp. isolated from effluent of an electroplating industry. Issue 5 (28th March 2017) - Punjabi, Kapil; Yedurkar, Snehal; Doshi, Sejal; Deshapnde, Sunita; Vaidya, Shashikant
Abstract : The aim of this study was to isolate and screen bacteria from soil and effluent of electroplating industries for the synthesis of silver nanoparticles and characterize the potential isolate. Soil and effluent of electroplating industries from Mumbai were screened for bacteria capable of synthesizing silver nanoparticles. From two soils and eight effluent samples 20 bacterial isolates were obtained, of these, one was found to synthesize silver nanoparticles. Synthesis of silver nanoparticle by bacteria was confirmed by undertaking characterization studies of nanoparticles that involved spectroscopy and electron microscopic techniques. The potential bacteria was found to be Gram‐negative short rods with its biochemical test indicating Pseudomonas spp . Molecular characterization of the isolate by 16S r DNA sequencing was carried out which confirmed its relation to Pseudomonas hibiscicola ATCC 19867. Stable nanoparticles synthesized were 50 nm in size and variable shapes as seen in SEM micrographs. The XRD and FTIR confirmed the crystalline structure of nanoparticles and presence of biomolecules mainly proteins as agents for reduction and capping of nanoparticles. The study demonstrates synthesis of nanoparticles by bacteria from effluent of electroplating industry. This can be used for large scale synthesis of nanoparticles by cost effective and environmentally benign mode of synthesis.